TEACHING VOCABULARY FOR YOUNG LEARNER BY USING SONGS AS THE MEDIA - Djamereng Jumharia (Institut Agama Islam Negeri Palopo, 2013)
Teaching young learners is not an easy job. Then, vocabulary is central of language teaching and learning. Therefore, in this paper, the writer would like to elaborate some theories and practice of teaching vocabulary by using English songs as the media. Dealing with the characteristic of young learner students, song is one of appropriate ways to create a good atmosphere to make teaching and learning process fresh and interesting